[11C]PBR28 radiotracer kinetics are not driven by alterations in cerebral blood flow. Issue 11 (November 2021) - Sander, Christin Y; Bovo, Stefano; Torrado-Carvajal, Angel; Albrecht, Daniel; Deng, Hongping; Napadow, Vitaly; Price, Julie C; Hooker, Jacob M; Loggia, Marco L
The positron emission tomography (PET) radiotracer [ 11 C]PBR28 has been increasingly used to image the translocator protein (TSPO) as a marker of neuroinflammation in a variety of brain disorders. Interrelatedly, similar clinical populations can also exhibit altered brain perfusion, as has been shown using arterial spin labelling in magnetic resonance imaging (MRI) studies. Hence, an unsolved debate has revolved around whether changes in perfusion could alter delivery, uptake, or washout of the radiotracer [ 11 C]PBR28, and thereby influence outcome measures that affect interpretation of TSPO upregulation. In this simultaneous PET/MRI study, we demonstrate that [ 11 C]PBR28 signal elevations in chronic low back pain patients are not accompanied, in the same regions, by increases in cerebral blood flow (CBF) compared to healthy controls, and that areas of marginal hypoperfusion are not accompanied by decreases in [ 11 C]PBR28 signal. In non-human primates, we show that hypercapnia-induced increases in CBF during radiotracer delivery or washout do not alter [ 11 C]PBR28 outcome measures. The combined results from two methodologically distinct experiments provide support from human data and direct experimental evidence from non-human primates that changes in CBF do not influence outcome measures reported by [ 11 C]PBR28 PET imaging studies and corresponding interpretations of the biological meaning of TSPO upregulation.